Das Ungültigwerden von Gesetzen in den griechischen Poleis (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
The article discusses the problem how and under which conditions the laws in ancient Greek poleis became invalid. It starts with a short preliminary survey about the general position of the Greeks against possible changes of their laws. So, on the one side, they praised the stability and unchangeability of the laws (I), on the other side in reality they accomodated themselves to the changeability of the laws (II). The core of the analysis starts with the problem how laws have actively been cancelled (III), divided in the sub-sections: blocks of laws, complete single laws, and parts of a law. It then considers the possibilities how laws could passively become invalid (IV) and dedicates the last section to the forms in which the legal force of the laws ceased (V). The collection of material is mainly limited to the archaic and classical periods, the term ‘law’ is narrowly defined and only occasionally suppliedby a look on polis-decrees.